Heterogeneity of commercialization gains in the rural economy. (7th December 2017) - Radchenko, Natalia; Corral, Paul; Winters, Paul
Abstract: Farmers in low‐income rural economies often fail to switch to cash crops from staple production despite the positive income effects of commercialization expected by policy makers. The literature suggests that market failures prevent households from cash crop adoption but remains inconclusive regarding farmers' motives and the effects of commercialization. This article contributes to the debate by offering an original approach to the analysis of commercialization outcomes and farmers' decisions. It consists of applying a model with essential heterogeneity and a semiparametric estimation technique to analyzing harvest value returns to cash cropping. Using Malawian data, we show considerable heterogeneity in harvest value returns to cash cropping both within and between groups of farmers choosing different crop portfolios. Importantly, the results imply rational choices based on comparative advantage considerations of farming households: farmers self‐select into the activity where they expect higher gains and adopt cash crops when facing weaker market barriers.